Creativity in Marketing: MSMEs Innovative Steps in Attracting Consumers - Santoso, Fuji; Sudarmiatin, Sudarmiatin; Wardana, Ludi Wishnu (West Science Journal Economic and Entrepreneurship, 2023)
Growth and success of micro, small and medium-sized enterprises (SMEs) are heavily influenced by product creativity and innovation. MSMES must develop high-quality goods to face increasing competition. These products must be able to meet the needs and demands of the changing market. The aim of this research is to identify progress in MSMEs products and emerging challenges. These small often have difficulties when it comes to product development; they still rely on old products for innovation, lack adequate capital, and do not have the right approach to developing their products. If a business wants to survive, they have to keep creating new products. Most of the income comes from MSMES, because the economy of the community can be helped by the existence of MSMES. But MSMES today is still limited in the presence of borrowing capital, because there are still many MSMES that have not been touched by the financial institutions.